The partitioning of delta 1-tetrahydrocannabinol into erythrocyte membranes in vivo and its effect on membrane fluidity. - Leuschner, J; Wing, DR; Harvey, D; Brent, G; Dempsey, C; Watts, A; Paton, W (1984)
delta 1-Tetrahydrocannabinol (delta 1-THC) has been quantified directly in erythrocyte membranes from drug-treated mice using gas chromatography/mass spectrometry. Concentrations of approximately 6 ng delta 1-THC/mg membrane protein (10(-5) M) were found when effects of the drug on behavior were prevalent. At these concentrations the drug produced a decrease in membrane order as measured by ESR.